HARMONISASI INTERPELASI DEWAN PERWAKILAN RAKYAT TERHADAP KEBIJAKAN PEMERINTAH - Shobahah, Nurush (Ahkam: Jurnal Hukum Islam, 2016)
The House of Representatives as a legislative body has threefunctions, namely the oversight function, legislative function, andthe budget function. One of the supervisory function s of The Houseof Representatives is the right of interpellation. As a law state, all ofthe processes of the state must be based on the law. Therefore, everypositive law must be obeyed. The constitutions or other regulationsof interpellation mention that the president may represent theanswers of interpellations. The frequent problem happening is theabsence of the president in the interpellation session. That problembecomes a relation problem between the president and the House ofRepresentatives which need to solve. Thus the right of interpellationas one of the implementations of the check-and-balance principle onthese two state institutions can run effectively. Based on the normativeprovision study it can be concluded that, to avoid the messy practices,the chapter which allows the president to have position in answeringthe interpellation court needs to be specified explicitly. As the result,the right of using interpellation can run well.Kata kunci: Dewan Perwakilan Rakyat, Interpelasi, Presiden